Fame-Led to Sympathy: Content Analysis of Felicya Angelista’s Statement Related to the Israeli-Palestinian Conflict Using Roland Barthes Semiotic Approach - Husen Mony; Ivanaldy Kabul; Angkie Yudistia; Nurhajati Lestari (Ikatan Sarjana Komunikasi Indonesia, 2024)
The video of Felicya Angelista discussing the Israeli-Palestinian conflict sparked controversy, with criticism directed at her for seemingly supporting Israel. The use of the word